Computer-Aided Generation of Bending Sequences for Die-Bending Machines - Hoffmann, Martin; Geißler, Uwe; Geiger, Manfred (Journal of Materials Processing Technology, Nr. 30, 1992)
The planning of bending sequences and the assigning of tools is a task that has to be done manually at the present time. As part of a computerized process-planning tool for sheet-metal parts, a bending-sequence generator has been developed. The bent part can be developed into the plane part automatically, technological data and know-how about the bending process and the press brake being included in this tool. The bending sequence generated by the computer can be simulated and altered ad libitum on a graphics screen. © 1992.
LFT Import::2019-08-05 (482)